Prevalence of Anti-HBc Antibodies among HBsAg Negative Individuals and Its Association with Occult Hepatitis B - Madhavan, Anitha; Sachu, Arun; Balakrishnan, Anu Kumar; Balakrishnan, Sobha; Vasudevapanicker, Jayalakshmi (Journal of Laboratory Physicians, 2021)
Introduction Hepatitis B virus (HBV) infection is an endemic in many Asian countries, and among the major routes of transmission, transfusion is the one that should be prevented. Occult HBV infection (OBI) is defined as the presence of HBV DNA in the absence of detectable HBsAg, with or without anti-HBV antibodies. The aim of this study was to detect the prevalence of anti-HBc total antibodies among the HB surface antigen (HBsAg) negative individuals by way of enzyme-linked immunosorbent assay (ELISA), and detect the presence of HBV DNA among the anti-HBc seropositives by polymerase chain reaction (PCR). Anti-HBs among the HBV DNA positives were also found out by enzyme-linked fluorescent assay (ELFA).Materials and Methods A total of 910 serum samples was subjected to initial screening for HBsAg by MERILISA HBsAg ELISA kits. The anti-HB core (HBc) total antibody titer was evaluated using MONOLISA ELISA (Biorad) kits. If found negative, the samples were discarded. If found positive, the samples underwent HBV DNA testing by nested PCR. Antibody to hepatitis B surface antigen (anti-HBs) was calculated among the DNA positives by ELFA.Results A total of 133 samples were positive for anti-HBC total antibody, resulting in an overall prevalence of 14.6%. Overall prevalence of HBV DNA among the anti-HBc seropositives was 2.2%.Conclusion Among the three HBV DNA positive patients, two belonged to the preoperative screening group, which is an alarming situation. Screening of blood for HBsAg has reduced the incidence of posttransfusion hepatitis, but HBV still remains the major source of transfusion transmitted infection in India.
Keywords: Anti-hepatitis B core total antibody; HBV DNA; Occult hepatitis B